Preparation, Characterization and Dermal Delivery of Methadone - Chin-Ping Kung; Bruno C. Sil; Jonathan Hadgraft; Majella E. Lane; Bhumik Patel; Renée McCulloch (MDPI AG, 2019)
The use of methadone for the management of pain has received great interest in recent years. Currently, oral and intravenous formulations are available for clinical use. Dermal delivery represents an attractive alternative route of administration for this drug as it is associated with comparatively fewer side effects. The first stage of the work was the preparation of methadone free base as this form of the drug is expected to permeate the skin to a greater extent than the hydrochloride salt. Subsequently the molecule was characterized with Nuclear Magnetic Resonance (NMR) and thermal analysis, the distribution coefficient was determined and solubility studies were conducted in a range of solvents. In vitro permeation and mass balance studies were conducted under finite dose conditions (5 μL/cm2) in porcine skin. The results confirmed the more favorable penetration of methadone free base compared with the salt. The highest cumulative amount of methadone (41 ± 5 μg/cm2) permeated from d-limonene (LIM). Ethyl oleate (EO), Transcutol® P (TC) and octyl salicylate (OSAL) also appear to be promising candidate components of dermal formulations for methadone base. Future work will focus on further formulation optimization with the objective of progressing to evaluation of prototype dosage forms in clinical trials.